Substance Use Disorder Education in Medical Schools: A Scoping Review of the Literature. (23rd July 2019) - Muzyk, Andrew; Smothers, Zachary P.W.; Akrobetu, Dennis; Ruiz Veve, Jennifer; MacEachern, Mark; Tetrault, Jeanette M.; Grupen, Larry
Abstract : Purpose: As medical schools adapt their curricula to prepare future physicians for the opioid crisis and for treating patients with substance use disorders (SUDs), educators should refer to courses described in the literature. This scoping review aimed to (1) provide a comprehensive evaluation and summation of peer-reviewed literature reporting on SUD education in medical schools globally, and (2) to appraise the research quality and educational outcomes reported in SUD education studies in medical schools. Method: The authors searched 6 databases (3 Ovid MEDLINE databases, Embase, ERIC, and Web of Science) from inception through May 25, 2018. Original English-language research studies focusing on medical students and describing SUD education in medical schools were included. The Medical Education Research Study Quality Instrument (MERSQI) was used to grade included studies. Results: Of 3, 178 articles identified, 43 met inclusion criteria. Studies were conducted in 9 countries. Most reported on educational interventions for tobacco (n = 20; 47%); others reported on interventions for SUDs broadly (n = 15; 35%), alcohol (n = 8; 19%), and opioids (n = 1; 2%). The mean MERSQI score was 12.27 (SD 2.30). Four studies (9%) reported on educational outcomes at the level of behaviors or patient or health care outcomes. The majority (n = 39; 91%) reported significant benefits. Conclusions: Educational interventions relating to SUDs were effective in improving medical students' knowledge, skills, and attitudes. Educators should develop courses that achieve higher-level educational outcomes, increase education on opioid use disorders, and focus on the greatest public health concerns.